Clinical Analysis of Demineralized Freeze Dried Bone Allograft and Deproteinized Bovine Bone Mineral Bone Graft Materials in a Bilateral Sinus Augmentation. - Stipho, Sarah. (2017)
Abstract: Sinus augmentation is often necessary in areas of the posterior maxilla where extensive alveolar bone resorption has occurred leading to insufficient bone height for adequate implant placement. The purpose of this study was to compare and analyze bone height and regeneration of two different bone graft materials in a split-mouth design: a demineralized freeze dried bone allograft incorporated with bone morphogenetic proteins and growth factors, Accell Connexus®, from Keystone Dental (Burlington, MA), and a deproteinized bovine bone mineral bone graft, Bio-Oss® product from Osteohealth, (Shirley, NY), which currently has been the standard material of choice. After obtaining informed consent and evaluating inclusion criteria, ten patients underwent a bilateral sinus augmentation procedure, with one side utilizing Accell Connexus® and the other side utilizing Bio-Oss® material. The piezoelectric system (Piezotome, Acteon, Paris, France) was used to perform the access for the sinus augmentation procedures to enable the grafting. After six months healing time, core biopsies were taken at the same location of implant placement and sent for analysis. Each patient underwent panoramic and CT radiographs to evaluate bone density, height and volume. Micro-CT analysis was performed for all core samples to evaluate degree of mineralization. No statistical significance was found in density or volume between the two materials. However, statistical significance was found for height changes with a p value of < 0.001. Bone graft materials used in the pneumatized sinus are needed for the placement of implants. The use of bone morphogenetic proteins and growth factors in these graft materials may suggest enhancement of healing but the loss in height due to resorption presents some disadvantage in these areas requiring implant placement.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Periodontology.; Advisor: Terrence Griffin.; Committee: Yong Hur, Khalid Al-Hezaimi, and Paul Stark.; Keywords: Dentistry, Surgery, and Health sciences.